Legislative Provisions Concerning Social Security for Online Ojek Drivers in Indonesia - Nurhadi, Imam (AKADEMIK: Jurnal Mahasiswa Humanis, 2023)
Indonesia's dense population is one of the triggers for the development of online transportation. In addition, many of Indonesia's workforce has low competence or non-skills, so the online motorcycle taxi profession is an option to be able to make ends meet. On the other hand, the status of online ojek drivers is partners, so there is no binding legal principle to be able to fight for the driver's welfare rights. Based on this background, this study aims to describe social security for online drivers based on aspects of legislation, so that it can be used as input for online transportation service providers to be able to make appropriate social security policies. To answer this, this research uses a qualitative approach with descriptive analysis. The method used to reveal the research phenomenon is the literature review method. Meanwhile, the data source used in this study is the law on work social security. The research topic is social security for online drivers in Indonesia. The results of the study show that in general the state has regulated labor welfare, as explained in Article 34 of the 1945 Act. However, specifically, the government has not provided regulations or laws that explain employment guarantees for workers in the online transportation sector. This condition is a loophole for online transportation entrepreneurs not to provide social security for their partners (online drivers).